A song for Lena - Hippely, Hilary Horder (Simon & Schuster Books for Young Readers, 1996)
Lena's grandmother tells about the time when her mother in Hungary shared some freshly made strudel with a beggar who repaid her hospitality with a beautiful song. Includes a recipe for apple strudel.